DEVELOPING AN INDONESIAN TEXTBOOK FOR NON-NATIVE LEARNERS OF INDONESIAN AT ELEMENTARY LEVEL - Sayit Abdul Karim (Universitas Katolik Indonesia Atma Jaya, 2015)
The present study aims at (1) exploring the learningmaterials which are available for non-native learners ofIndonesian who learn Indonesian at Elementary level, andtheir weaknesses; (2) examining and developing thealternative model to suit the needs of non-native learners ofIndonesian to communicate intensively in Indonesian; and(3) evaluating the effectiveness of the learning material usedfor non-native learners of Indonesian at Elementary level.The research design in this study was research anddevelopment (R&D) model by Borg and Gall (1983: 775).The subjects of the try out were six Darmasiswa students atUNNES BIPA program in the academic year of 2012/2013.They were one student from Japan, one from Poland, twofrom Estonia, one from Czechoslovakia, and one studentfrom the Netherlands.The product developed has been examined in the tryoutsession. Students’ achievement was improved after usingthe product. The improvement of students’ achievement wasabout 20% to 25%. Finally, it can be concluded that theIndonesian textbook developed for non-native learners ofIndonesian at Elementary level is helpful, effective, andappropriate to be used in the Indonesian to speakers of otherlanguages program.Keywords: Material Development, Elementary level,Indonesian textbook, Non-native Learners ofIndonesian.